Seasonal occupancy of the thermal plume of a spring tributary to the South Fork Roanoke River, Virginia. - Steven L Powers; Michael M Calvert; Charlotte M Spaulding (Southeastern Fishes Council Proceedings, 2024)
Detection of temperate stream fishes varies widely across seasons as streams teeming with life in summer often appear empty during winter sampling efforts. While much literature documents the disproportionate use of the thermal plumes of spring tributaries by cold water fishes during summer, few studies have investigated occupancy of those habitats by warm water fishes in winter. We conducted quantitative snorkeling observations within the near uniform temperatures (10-14oC) of the thermal plume of a spring tributary to the South Fork Roanoke River across seasons and compared number of fishes observed and species richness to control observations made just upstream of the spring tributary and downstream of the spring tributary outside of the thermal plume. Outside of the thermal plume, species richness and number of fishes observed increased with stream water temperature ranging from 2-25oC. Within the thermal plume of the spring tributary, non-salmonid species richness and number of fishes observed were greater during colder months than during warmer months. This suggests warm water fishes were disproportionately using the thermal plume of the spring tributary during the cold winter months. The warmer water of the plume likely serves as a thermal refuge allowing elevated metabolism that aids feeding, growth, and gamete development when stream water would otherwise leave these ectotherms largely dormant. As such, it appears these spring tributaries are especially important habitats for warm water stream fishes in addition to the well documented importance of these habitats for spring endemics and cold water fishes.
Keywords: Winter; groundwater; springs; warm water fishes; thermal refuge